A community-based study on the prevalence of depression and its determinants among elderly diabetic patients in a rural area of West Bengal, India - Pal, Jayita; Pramanik, Mrinal; Ghosh, Koustab; Krishna, Nandu; Ghosh, Manoj; Chawale, Shubham Vivekanand (International Journal Of Community Medicine And Public Health, 2025)
Background: Type 2 diabetes mellitus often coexists with depressive symptoms and thereby complicating the overall outcome. Elderly diabetic patients are particularly at risk of having poor quality of life because of coexisting depression, which many a time is often not diagnosed and cared for. The current study aimed to estimate the prevalence and identify the determinants of depression among elderly diabetic patients in a rural area of West Bengal. Methods: A community-based cross-sectional study was conducted in the Haringhata block, Nadia district, West Bengal, with the help of a predesigned and pretested semi-structured questionnaire, under which depression was measured by the patient health questionnaire 9 (PHQ-9). A total of 200 elderly diabetic patients were included by simple random sampling from the sampling frame available in the health and wellness centres of the block. The data, thus collected, were entered and analysed in Jamovi software. Results: The majority (55%) of the study participants were suffering from minimal to mild depression, while nearly half (45%) were suffering from moderate and higher grades of depression. Multivariate analysis revealed that the number of pills taken per day, medication adherence, physical activity, socio-economic status, and educational level were significant predictors of depression among the study participants. Conclusions: Strict medication adherence, practice of prescription of a minimum number of pills for glycemic control, and involvement in regular physical activity are the need of the hour for prevention and alleviation of depression among elderly diabetic patients and thereby achieving a better quality of life.